1255 IMPROVING COMMUNICATION BETWEEN NEXT OF KIN AND MEDICAL STAFF FOR OUR MOST VULNERABLE PATIENTS: A QUALITY IMPROVEMENT PROJECT. (16th January 2023) - Montandon, S; Win, S; Jones, S; Bello, I; Amin, A; Khan, S; Biswas, S; Aperios, G; Gibson, M; Yahia, G
Abstract: Background: This project was completed by a team of junior doctors working across two general medical wards at Queen Alexandra Hospital. Introduction: Due to persistently high bed occupancy, patients are increasingly subject to multiple moves, increasing the risk of missed or delayed communication (Toye C et al, Clin interv aging, 2019, 14, 2223-2237). Importantly, families who receive good communication from staff are more likely to feel satisfied with the care of their loved one (Ersek M et al, J pain symptom manage, 2021, 62(2), 213–222). Our aim was to increase the occurrence and comprehensiveness of documented discussions between next of kin (NOK) and the medical team, especially in vulnerable patients who may be unable to advocate for themselves. Methods: We conducted a retrospective, cross-sectional analysis of patient notes across two PDSA cycles. NICE guidelines NG27, NG97 and NG96 provided an audit standard. Patients were identified as at-risk of poor communication if diagnosed with dementia, cognitive impairment, addiction, learning difficulties or needing an interpreter. Targeted intervention prior to re-audit included education of the medical team and introduction of a written prompt within the patient's notes. Results: 25/55 patients were identified as at-risk in cycle one, with 39/71 patients at-risk in cycle two. Post-intervention, the number of at-risk patients with a documented NOK discussion increased from 74% to 82%. Patient treatment plan discussions increased from 81% to 97%. Discussions, where applicable, regarding escalation of care, Deprivation of Liberty Safeguards (DoLS), capacity and Mental Health Act (MHA) slightly decreased. Conversations regarding patient consent for data sharing were rarely documented. Conclusion: Our intervention increased the proportion of documented patient discussions; however, it did highlight the need to improve the frequency of documented conversations surrounding escalation of care, DoLS, capacity and MHA. This has provided impetus for further improvement projects.